Three-Dimensional-Printed Titanium Versus Polyetheretherketone Cages for Lumbar Interbody Fusion: A Systematic Review of Comparative In Vitro, Animal, and Human Studies - Neal A. Patel; Sinead O’Bryant; Christopher D. Rogers; Sachiv Chakravarti; Julian Gendreau; Nolan J. Brown; Zach A. Pennington; Neill B. Hatcher; Luis Daniel Diaz-Aguilar; Martin H. Pham (Neurospine, 2023)
Interbody fusion is a workhorse technique in lumbar spine surgery that facilities indirect decompression, sagittal plane realignment, and successful bony fusion. The 2 most commonly employed cage materials are titanium (Ti) alloy and polyetheretherketone (PEEK). While Ti alloy implants have superior osteoinductive properties they more poorly match the biomechanical properties of cancellous bones. Newly developed 3-dimensional (3D)-printed porous titanium (3D-pTi) address this disadvantage and are proposed as a new standard for lumbar interbody fusion (LIF) devices. In the present study, the literature directly comparing 3D-pTi and PEEK interbody devices is systematically reviewed with a focus on fusion outcomes and subsidence rates reported in the in vitro, animal, and human literature. A systematic review directly comparing outcomes of PEEK and 3D-pTi interbody spinal cages was performed. PubMed, Embase, and Cochrane Library databases were searched according to PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines. Mean Newcastle-Ottawa Scale score for cohort studies was 6.4. A total of 7 eligible studies were included, comprising a combination of clinical series, ovine animal data, and in vitro biomechanical studies. There was a total population of 299 human and 59 ovine subjects, with 134 human (44.8%) and 38 (64.4%) ovine models implanted with 3D-pTi cages. Of the 7 studies, 6 reported overall outcomes in favor of 3D-pTi compared to PEEK, including subsidence and osseointegration, while 1 study reported neutral outcomes for device related revision and reoperation rate. Though limited data are available, the current literature supports 3D-pTi interbodies as offering superior fusion outcomes relative to PEEK interbodies for LIF without increasing subsidence or reoperation risk. Histologic evidence suggests 3D-Ti to have superior osteoinductive properties that may underlie these superior outcomes, but additional clinical investigation is merited.